The Experience of architecture - Plummer, Henry 1946- (Thames & Hudson Ltd, 2016)
How does the experience of turning a door handle, opening a door from one space to lead into another, affect us? This book aims to understand how these everyday acts are influenced by architectural form, a concept that is vital for all architects to grasp if our buildings are to be anything more than a commercial or aesthetic enterprise. It considers how specific built elements and volumes can sustain or deny our powers of decision. Each chapter focuses on a different aspect of our daily interactions with architecture, looking at stairs, floors and paths, moving interior spaces, perception and perspective, transparency and the relationship between a building and its setting. This book is not just for architects and designers engaged in the production of space, but for all those who seek a richer understanding of their place in the built world.